1994
DOI: 10.3109/00016349409006251
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of 5-aminosalicylic acid and N-acetyl-5-aminosalicylic acid in fetal and maternal body fluids during treatment with different 5-aminosalicylic acid preparations

Abstract: The study indicates that treatment with pure 5-ASA preparations in conventional doses is without risk to the fetus and the newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…According to the FDA, they are category B drugs, except for olsalazine (category C). Both 5-ASA and its active metabolite N-acetyl 5-ASA can cross the placenta (6). However, studies in both animals and humans have not demonstrated any teratogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…According to the FDA, they are category B drugs, except for olsalazine (category C). Both 5-ASA and its active metabolite N-acetyl 5-ASA can cross the placenta (6). However, studies in both animals and humans have not demonstrated any teratogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…La leche materna excreta la mesalazina, que no significa un mayor riesgo para el niño 144 . Aunque es poco frecuente, puede aparecer diarrea en el recién nacido, en este caso habría que interrumpir la lactancia 145 .…”
Section: A) Salicilatosunclassified
“…There is no significant change in congenital abnormalities, abortions or fetal distress with conventional 5-aminosalicylic acid treatment [31][32][33] . Mesalamine is excreted in breast milk, but does not pose a significant risk to the baby [34] .…”
Section: -Asa (Mesalamine)mentioning
confidence: 99%